Multi-solid waste synergic composite solidifying agent suitable for high-sulfur heavy metal composite pollution and application thereof
Patent Information
- Application Number
- CN202611105554.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-09
AI Technical Summary
[0007]本发明的目的:针对现有技术存在的诸多缺陷,本发明提供一种适配高硫重金属复合污染的多固废协同复合固化剂及其应用,解决传统固化剂高硫工况失效、固化体开裂、强度不足、长效稳定性差、无法资源化焦化及脱硫固废、偏高土改良效果差的行业难题,实现工业固废资源化、污染土体结构改良、重金属及硫污染物长效稳定的多重技术突破
1、突破传统技术工况局限,实现高硫复合污染长效稳定。本发明摒弃现有技术强氧化体系设计,独创无水硫代硫酸钠还原缓冲体系,可稳定亚硫酸盐、硫化物组分,维持DDTC螯合结构稳定,彻底解决传统固化剂无法适配焦化、脱硫等高硫复杂工况、污染物易二次溶出的技术难题。
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of contaminated site remediation, industrial solid waste resource utilization and heavy metal stabilization technology, specifically involving a multi-solid waste synergistic composite solidifying agent adapted to coking high-sulfur, heavy metal composite contaminated soil and desulfurization solid waste and its application. Background Technology
[0002] Coking sites and desulfurization waste disposal sites commonly suffer from complex pollution problems involving high sulfur content and multiple metals. These sites also often contain high-alumina silicate clay (high-alumina soil), presenting engineering and environmental challenges such as loose soil structure, poor water stability, low bearing capacity, easy cracking after solidification, and easy secondary leaching of pollutants. Traditional solidification and stabilization materials are mainly divided into two categories: cement-lime inorganic cementitious materials and single organic chelate solidification materials. Both have significant technical shortcomings and are difficult to adapt to the remediation needs of complex industrial contaminated sites.
[0003] Traditional inorganic solidification materials such as cement and lime can only achieve simple soil hardening and alkaline precipitation solidification of heavy metals. The solidified body has large shrinkage deformation, is easy to crack, has poor long-term leaching resistance, and cannot be adapted to high sulfur pollutant matrix. In high sulfur environment, it is prone to problems such as strength shrinkage and excessive re-dissolution of pollutants. At the same time, it cannot achieve the co-utilization of industrial solid waste resources, resulting in high disposal costs and low resource utilization rate.
[0004] Existing organic chelation solidification technologies mostly employ organic sulfur chelating agents such as sodium diethyldithiocarbamate (DDTC), relying on a single chemical complexation effect to fix heavy metals. This is currently the most widely used technical solution in the field of heavy metal stabilization. Existing publicly available technology (CN202411261674.7 A heavy metal solidifying agent for treating arsenic-containing fly ash and its application) discloses a fly ash-specific solidification system. This system is composed of an oxidative stabilization system and an organic chelation system, with bleaching powder, carbide slag, composite iron salts, activated carbon, and chitosan derivatives as basic components, supplemented by organic chelating agents such as DDTC. Through oxidative modification, alkaline precipitation, physical adsorption, and the synergistic effect of organic chelation, it achieves the stable solidification of arsenic and conventional heavy metals in municipal solid waste incineration fly ash.
[0005] However, this existing technology has inherent and unavoidable technical flaws: First, its application scenarios are extremely limited, only suitable for the treatment of arsenic-containing fly ash from municipal solid waste incineration in low-sulfur environments. It is not designed for complex industrial conditions such as high-sulfur contaminated soil from coking, calcium sulfite solid waste from desulfurization, and soil contaminated with high aluminosilicate content, resulting in extremely poor adaptability to various working conditions. Secondly, the technology has a single function, only having the function of chemically stabilizing and fixing pollutants, without the functions of soil hydration and hardening, structural improvement, and bearing capacity enhancement, and therefore cannot achieve soil reinforcement and remediation of contaminated sites. Third, the system has significant defects in environmental adaptability. When the strong oxidizing system of bleaching powder is applied to a high-sulfur polluted matrix, it will rapidly oxidize sulfide and sulfite components, destroy the chelated and stable structure of heavy metals, and cause secondary leaching of pollutants, making it impossible to guarantee the long-term effectiveness of solidification. Fourth, there is no solid waste resource utilization design, and industrial solid waste is not used as the core matrix raw material, resulting in low resource utilization rate and high disposal cost. Fifth, the lack of microstructure regulation means that the solidification of pollutants relies solely on the adsorption of macropores in activated carbon. There are no methods to modify the micropores to make them dense. The solidified body has large pores, and the risk of heavy metal leaching is high under long-term rainwater leaching and environmental erosion. Sixth, it lacks engineering adaptability. Using chitosan derivatives as functional additives only has chelation and flocculation effects, which cannot solve engineering problems such as agglomeration of ultrafine powders and uncontrolled hydration rate, making it difficult to adapt to large-area in-situ repair construction scenarios.
[0006] In summary, existing solidification technologies generally suffer from technical bottlenecks such as limited functionality, poor adaptability to high-sulfur conditions, easy cracking of solidified bodies, insufficient long-term stability, inability to synergistically utilize industrial solid waste, and poor soil improvement effects. The industry urgently needs an integrated composite solidification agent that can adapt to high-sulfur heavy metal complex pollution, take into account soil structure improvement, solid waste resource utilization, and long-term leaching resistance. Summary of the Invention
[0007] The purpose of this invention is to address the numerous shortcomings of existing technologies by providing a multi-solid waste synergistic composite solidifying agent adapted to high-sulfur and heavy metal composite pollution and its application. This invention solves the industry problems of traditional solidifying agents failing under high-sulfur conditions, cracking of the solidified body, insufficient strength, poor long-term stability, inability to utilize coking and desulfurization solid wastes for resource recovery, and poor soil improvement effects. It achieves multiple technological breakthroughs in industrial solid waste resource recovery, soil structure improvement, and long-term stability of heavy metals and sulfur pollutants.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: A multi-solid waste synergistic solidification agent suitable for high-sulfur heavy metal complex pollution is composed of the following components: calcium sulfite, metasomatic clay, fly ash, aluminosilicate, sodium diethyldithiocarbamate, anhydrous sodium thiosulfate, aluminum silicate, calcium oxide, sodium polyacrylate, nano silica, calcium sulfate dihydrate, and silicate clinker.
[0009] The curing agent constructs four synergistic functional systems: a reduction and sulfur stabilization system, a multi-calcium source crack-resistant cementing system, a solid waste geological polymer framework system, and a nano-dense modification system. The anhydrous sodium thiosulfate constitutes a reducing sulfur stabilizing system, which is used to stabilize calcium sulfite and sulfide components in a high-sulfur polluted matrix, inhibit the oxidative decomposition of sulfur, protect the heavy metal chelate structure from oxidative damage, and solve the defect of secondary leaching of pollutants by oxidative curing agents under high-sulfur conditions. The calcium oxide, silicate clinker, calcium sulfate dihydrate and calcium sulfite together constitute a multi-calcium source gradient hydration crack-resistant cementitious system. Through hydration, ettringite microcrystals are generated to produce a micro-expansion effect, which compensates for the drying shrinkage deformation of the solidified body and achieves early strength, high strength and crack resistance stability of the solidified body. The fly ash, aluminosilicate, and aluminum silicate undergo a geological polymerization reaction under alkaline activation conditions to form a stable Si-O-Al three-dimensional gel network framework, realizing the resource utilization of industrial solid waste and the reinforcement of high soil structures. The nano-silica and aluminum silicate synergistically form a nano-microporous sealing system, which fills the micropores and microcracks inside the solidified body in multiple stages, blocks the migration channels of pollutant ions, and improves the long-term leaching resistance of the solidified body.
[0010] Further, the components are composed of the following parts by weight: 15-24 parts calcium sulfite, 12-25 parts metacarbohydrate, 12-28 parts fly ash, 6-30 parts aluminosilicate, 2-4 parts sodium diethyldithiocarbamate, 1-3 parts anhydrous sodium thiosulfate, 0.5-8 parts aluminum silicate, 0.1-10 parts calcium oxide, 0.1-1.5 parts sodium polyacrylate, 0.1-2.5 parts nano silica, 7-22 parts calcium sulfate dihydrate, and 2-4 parts silicate clinker.
[0011] Furthermore, the fly ash is ultrafine dry fly ash from coking plant coal, the aluminum silicate is ultrafine aluminum silicate powder, the calcium oxide is ultrafine calcium oxide powder, the effective calcium oxide content is ≥90%, and the sodium polyacrylate is in powder form.
[0012] Furthermore, the curing agent is an integrated dry powder compound system without liquid additives. The components work synergistically to construct a gelation hardening skeleton, a solid waste activation system, a high-sulfur stabilizing buffer system, a heavy metal chelation system, a micro-dense modification system, and an engineering performance regulation system, respectively.
[0013] The mechanisms of action of each core component of this invention are as follows: 1. Multi-calcium source composite cementitious system: It is composed of calcium oxide ultrafine powder, silicate clinker, calcium sulfate dihydrate, and calcium sulfite. The ultrafine calcium oxide rapidly hydrates to generate calcium hydroxide, providing a strongly alkaline activation environment and quickly achieving initial hardening of the soil. The silicate clinker continuously hydrates, ensuring the long-term stability of the mechanical strength of the solidified body. The calcium sulfate dihydrate and calcium sulfite form a composite sulfate system, which hydrates to generate ettringite microcrystals, producing a micro-expansion effect, accurately compensating for the hydration shrinkage deformation of calcium oxide, and completely solving the problems of cracking and strength reduction of the solidified body.
[0014] 2. Multi-solid waste activation matrix system: Using ultrafine dry fly ash from coking plant coal, aluminosilicate, and ultrafine aluminum silicate as core active silicon-aluminum sources, a geological polymerization reaction occurs under strong alkali activation to construct a stable Si-O-Al three-dimensional gel network framework, realizing the large-scale resource utilization of coking solid waste and desulfurization calcium sulfite solid waste, while specifically improving the engineering defects of soil with high aluminosilicate content, such as looseness, softening, and insufficient bearing capacity.
[0015] 3. High-sulfur reducing buffer stabilization system: The addition of anhydrous sodium thiosulfate creates a weak reducing buffer environment, which can stabilize calcium sulfite and various sulfide components in the system, inhibit the oxidation and loss of sulfur, and avoid the destruction of heavy metal chelate structure under high-sulfur conditions. This fundamentally solves the problems of failure of traditional oxidative curing agents in high-sulfur environments and secondary leaching of pollutants.
[0016] 4. High-efficiency heavy metal chelation system: Sodium diethyldithiocarbamate is used as a dedicated chelating agent, which can form stable and insoluble complexes with various heavy metals such as lead, cadmium, zinc, copper, and mercury, to achieve chemical closed-loop fixation of heavy metals. Combined with the physical encapsulation of the gel skeleton, a dual solidification mechanism of "chemical chelation + physical blocking" is formed.
[0017] 5. Nano-micro dense modification system: Introducing nano-silica and ultrafine aluminum silicate powder, utilizing the characteristics of nano- and ultrafine particles, precisely filling the micron and nano-scale micropores and microcracks of the solidified body, blocking the dissolution channels of pollutant ions in multiple stages, and significantly improving the anti-permeability, anti-carbonization, and anti-leaching properties of the solidified body.
[0018] 6. Engineering performance control system: The addition of sodium polyacrylate powder can effectively break up the agglomeration structure of nano and ultrafine powders, fully release the gelling and activation activities of each component, and at the same time precisely control the hydration rate of the system, extend the construction window period, reduce slurry bleeding and stratification, and is suitable for engineering scenarios such as large-area in-situ soil remediation and bulk solid waste disposal.
[0019] The present invention also provides the application of the composite curing agent in the remediation of coking sites contaminated with high sulfur and heavy metals, the stabilization and disposal of desulfurization solid waste, and the improvement of soil contaminated with high aluminosilicate.
[0020] Compared with the prior art, the present invention has comprehensive and outstanding substantive features and significant progress, and the specific beneficial effects are as follows: 1. Breaking through the limitations of traditional technologies and operating conditions, achieving long-term stability of high-sulfur complex pollution. This invention abandons the strong oxidation system design of existing technologies and creates a unique anhydrous sodium thiosulfate reducing buffer system, which can stabilize sulfite and sulfide components, maintain the stability of the DDTC chelate structure, and completely solve the technical problems of traditional solidifying agents being unable to adapt to complex high-sulfur operating conditions such as coking and desulfurization, and the easy secondary leaching of pollutants.
[0021] 2. Constructing a multiphase rigid cementitious skeleton to solve the problems of cracking and insufficient strength in the solidified body. Compared with the single alkaline precipitation mechanism of existing technologies, this invention adopts an ultrafine multi-calcium source composite system, combined with the long-term hydration of silicate clinker and sulfate micro-expansion compensation technology, to achieve early strength, high strength, anti-drying shrinkage, and crack-free solidified body, which also has the functions of soil hardening and foundation improvement, overcoming the shortcomings of traditional chelated curing agents that have no structural reinforcement capabilities.
[0022] 3. Achieving collaborative resource utilization of industrial solid waste, achieving energy conservation, environmental protection, and low cost. This invention uses industrial solid wastes such as coking ultrafine fly ash and desulfurized calcium sulfite as core matrix raw materials to construct a solid waste-based geopolymer gel system, realizing large-scale solid waste disposal, replacing traditional high-purity chemical raw materials, significantly reducing remediation and disposal costs, and achieving "waste-to-waste treatment and resource recycling".
[0023] 4. Precisely adaptable to high-alumina soil improvement, broadening application scenarios. This invention uses alkali-activated polymerization of active silica-alumina components to specifically improve the engineering defects of high-alumina silicate soil, such as poor water stability, low bearing capacity, and easy softening. It can be adapted to multiple scenarios, including industrial contaminated sites, special soil improvement, and solid waste disposal, and its versatility far exceeds that of existing single-function solidification technologies.
[0024] 5. Nanoscale multi-level densification significantly improves long-term environmental stability. This invention employs nano-silica and ultrafine powder multi-level pore sealing technology to construct a dual seepage barrier of gel framework + nanoparticle filling. Compared with the existing technology of activated carbon single macroporous adsorption mode, the density, leaching resistance and aging resistance of the solidified body are greatly improved, which can achieve long-term safety and stability of contaminated sites.
[0025] 6. Strong engineering adaptability and easy for large-scale construction. This invention is an integrated dry powder compounding system, which is convenient for storage and transportation. Combined with sodium polyacrylate dispersion and regulation components, it solves the problems of ultrafine powder agglomeration and hydration runaway. It has a long construction window period and good slurry uniformity, making it suitable for large-area in-situ remediation and batch solid waste disposal projects, with extremely high practicality.
[0026] 7. Strong technological synergy, not simply the superposition of components. This invention deeply couples six major technology systems: solid waste geological polymerization, multi-calcium source crack-resistant gelation, high sulfur reduction stabilization, nano-dense modification, heavy metal chelation and fixation, and engineering performance regulation. Each component works synergistically and complements each other, achieving comprehensive technical effects that cannot be achieved by a single existing technology, demonstrating outstanding creativity and advancement. Detailed Implementation
[0027] The present invention will be further described in detail and completely below with reference to specific embodiments. The following embodiments are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.
[0028] All raw materials used in this invention are industrial dry powders, including calcium oxide, ultrafine aluminum silicate, and nano silica, which are all ultrafine nanoscale powders. All components can be uniformly mixed at room temperature to prepare an integrated composite curing agent without the need for preheating, pre-dissolving, or adding external liquid additives. The preparation process is simple and the construction is convenient. Example
[0029] This example presents a multi-solid waste synergistic solidification agent suitable for high-sulfur + heavy metal compound pollution. By weight, it consists of the following components: 18 parts calcium sulfite, 22 parts metasomatic clay, 24 parts ultrafine dry fly ash from coking plant coal, 8 parts aluminosilicate, 2.5 parts sodium diethyldithiocarbamate, 1.5 parts anhydrous sodium thiosulfate, 3 parts ultrafine aluminum silicate powder, 8 parts ultrafine calcium oxide powder, 1 part sodium polyacrylate powder, 1.5 parts nano silica, 8 parts calcium sulfate dihydrate, and 2.5 parts silicate clinker.
[0030] Preparation method: Put all the above dry powder components into a closed dry powder mixer and stir at room temperature for 15-20 minutes until the powder is uniform, without agglomeration or color difference. Seal and store in a moisture-proof environment to obtain the finished composite curing agent.
[0031] Application method: For heavily polluted coking soil with high sulfur content and lead, cadmium and zinc content, the solidifying agent dosage is 8% of the dry mass of the polluted soil. After adding water and mixing thoroughly, it is spread, compacted and leveled, and cured at room temperature. The mechanical properties and pollutant leaching performance are tested at 7 days and 28 days respectively. Example
[0032] This example describes a multi-solid waste synergistic solidification agent suitable for high-sulfur heavy metal complex pollution. By weight, it consists of the following components: 22 parts calcium sulfite, 24 parts metasomatic clay, 16 parts ultrafine dry fly ash from coking plant coal, 6 parts aluminosilicate, 2 parts sodium diethyldithiocarbamate, 2 parts anhydrous sodium thiosulfate, 7 parts ultrafine aluminum silicate powder, 6 parts ultrafine calcium oxide powder, 1 part sodium polyacrylate powder, 2 parts nano silica, 9 parts calcium sulfate dihydrate, and 3 parts silicate clinker.
[0033] This embodiment focuses on enhancing the disposal of desulfurized solid waste and improving the structure of high-alumina soil, making it suitable for the remediation of desulfurized calcium sulfite solid waste storage sites and high-alumina soil contaminated sites. The preparation method is the same as in Example 1, with the solidifying agent dosage being 6% of the dry mass of the contaminated matrix, and the curing and testing conditions are consistent. Example
[0034] This example describes a multi-solid waste synergistic solidification agent suitable for high-sulfur heavy metal composite pollution. By weight, it consists of the following components: 15 parts calcium sulfite, 20 parts metasomatic clay, 28 parts ultrafine dry fly ash from coking plant coal, 7 parts aluminosilicate, 2.5 parts sodium diethyldithiocarbamate, 1.5 parts anhydrous sodium thiosulfate, 5 parts ultrafine aluminum silicate powder, 7 parts ultrafine calcium oxide powder, 1.2 parts sodium polyacrylate powder, 2 parts nano silica, 8 parts calcium sulfate dihydrate, and 2.8 parts silicate clinker.
[0035] This embodiment increases the proportion of solid waste admixture, balancing treatment effectiveness and economy, and is suitable for the remediation of various types of soil contaminated with moderate to light levels of high sulfur and heavy metals. The preparation method is the same as in Example 1, with the solidifying agent dosage being 5% of the dry mass of the contaminated matrix.
[0036] The arsenic-containing fly ash-specific heavy metal solidifying agent disclosed in the background technology of this invention was used as a comparative example. Its components, by weight, are: 10 parts bleaching powder, 30 parts calcium carbide slag, 8 parts composite iron salt, 5 parts activated carbon, 7 parts chitosan derivative, and 3 parts sodium diethyldithiocarbamate. Using the same agent dosage and curing conditions, high-sulfur coking contaminated soil was solidified, and performance comparison tests were conducted simultaneously.
[0037] Effect verification and comparative analysis Under the same curing environment and dosage conditions, the cured samples of each embodiment and comparative example were tested for 28 days. The main test indicators included: unconfined compressive strength, soil surface cracking, leaching concentration of heavy metals (Pb, Cd, Zn), and leaching concentration of sulfides and sulfites. The test was conducted in accordance with the "Pollution Control Standard for Municipal Solid Waste Landfills" (GB 16889-2024) and relevant geotechnical testing specifications. The test results are as follows: 1. Mechanical properties and crack resistance: The unconfined compressive strength of the solidified soil in Examples 1-3 of this invention is ≥2.8MPa after 28 days. The soil has excellent integrity, with no shrinkage cracks or peeling on the surface, and excellent structural integrity and stability. In contrast, the solidified sample in the comparative example has a strength of only 0.9MPa after 28 days. The soil structure is loose, with a large number of fine shrinkage cracks on the surface, and poor structural stability. It cannot meet the requirements for soil reinforcement and backfilling in industrial sites.
[0038] 2. Heavy metal stabilization performance: In the contaminated soil treated in Examples 1-3 of this invention, the leaching concentrations of heavy metals such as Pb, Cd, and Zn were all far below the national standard limits, and the overall solidification and stabilization rate of heavy metals was ≥99%. In contrast, under high sulfur pollution conditions, the heavy metal chelate structure was oxidized and destroyed, the heavy metal leaching concentration exceeded the standard, and the solidification and stabilization function failed.
[0039] 3. Stability of sulfur pollutants: Examples 1-3 of this invention can effectively stabilize sulfites and sulfides in the system, with no obvious leaching of sulfur pollutants and no risk of secondary pollution; the comparative example shows that the sulfur components are oxidized and decomposed by the strong oxidizing system, resulting in a large amount of sulfur pollutants being dissolved, which is completely unsuitable for high sulfur pollution conditions.
[0040] 4. Soil improvement performance: This invention can significantly improve the density, water stability and bearing capacity of high-alumina soil, and thoroughly improve the engineering defects of high-alumina soil softening and loose structure when exposed to water; the comparative example has no soil structure improvement capability and cannot achieve the foundation reinforcement and remediation of contaminated sites.
[0041] In summary, this invention, through deep synergistic compounding of multi-component, multi-functional systems, and relying on its original reducing buffer sulfur stabilization system, multi-calcium source micro-expansion anti-cracking gelling system, solid waste geological polymerization framework system, and nano-level multi-level dense modification system, systematically overcomes the technical bottlenecks of existing solidification technologies, such as poor adaptability to high-sulfur conditions, easy cracking of solidified bodies, low mechanical strength, insufficient long-term anti-leaching stability, inability to utilize industrial solid waste resources, and inability to improve the defects of high-sulfur soil engineering. It is suitable for various industrial scenarios with high-sulfur heavy metal composite pollution, such as coking and desulfurization. It has strong technical synergy, stable treatment effect, and outstanding engineering practicality, and has significant technical advancement and creativity.
[0042] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, or simple improvements made to the present invention within the inventive concept and core principles should be included within the scope of protection of the present invention.
Claims
1. A multi-solid waste synergistic solidification agent suitable for high-sulfur heavy metal complex pollution, characterized in that, It is composed of the following components: calcium sulfite, meta-high clay, fly ash, aluminosilicate, sodium diethyldithiocarbamate, anhydrous sodium thiosulfate, aluminum silicate, calcium oxide, sodium polyacrylate, nano silica, calcium sulfate dihydrate, and silicate clinker. The curing agent constructs four synergistic functional systems: a reduction and sulfur stabilization system, a multi-calcium source crack-resistant cementing system, a solid waste geological polymer framework system, and a nano-dense modification system. The anhydrous sodium thiosulfate constitutes a reducing sulfur stabilizing system, which is used to stabilize calcium sulfite and sulfide components in a high-sulfur polluted matrix, inhibit the oxidative decomposition of sulfur, and protect the heavy metal chelate structure from oxidative damage. The calcium oxide, silicate clinker, calcium sulfate dihydrate and calcium sulfite together constitute a multi-calcium source gradient hydration crack-resistant cementitious system. Through hydration, ettringite microcrystals are generated to produce a micro-expansion effect, which compensates for the drying shrinkage deformation of the solidified body and achieves early strength, high strength and crack resistance stability of the solidified body. The fly ash, aluminosilicate, and aluminum silicate undergo a geological polymerization reaction under alkaline activation conditions to form a stable Si-O-Al three-dimensional gel network framework, which is used for the resource utilization of industrial solid waste and the reinforcement of high-soil structures. The nano-silica and aluminum silicate synergistically form a nano-dense modification system, which fills the micropores and microcracks inside the solidified body in multiple stages, blocks the migration channels of pollutant ions, and improves the long-term leaching resistance of the solidified body.
2. The multi-solid waste synergistic composite solidifying agent adapted to high-sulfur heavy metal composite pollution according to claim 1, characterized in that, The components are composed of the following parts by weight: 15-24 parts calcium sulfite, 12-25 parts metacarbohydrate, 12-28 parts fly ash, 6-30 parts aluminosilicate, 2-4 parts sodium diethyldithiocarbamate, 1-3 parts anhydrous sodium thiosulfate, 0.5-8 parts aluminum silicate, 0.1-10 parts calcium oxide, 0.1-1.5 parts sodium polyacrylate, 0.1-2.5 parts nano silica, 7-22 parts calcium sulfate dihydrate, and 2-4 parts silicate clinker. The components are a fully dry powder integrated compound system, without liquid additives or on-site secondary mixing components. All raw materials are uniformly mixed and shaped into dry powder.
3. The multi-solid waste synergistic solidification agent adapted to high-sulfur heavy metal composite pollution according to claim 2, characterized in that: The calcium oxide, nano silica, and aluminum silicate are ultrafine nano-sized powders with a particle size ≤500nm, used to achieve micropore filling and structural densification modification; the fly ash is ultrafine dry fly ash from coking plant coal, and the effective calcium oxide content in the calcium oxide is ≥90%.
4. The multi-solid waste synergistic solidification agent adapted to high-sulfur heavy metal composite pollution according to claim 1, characterized in that: The calcium sulfate dihydrate and calcium sulfite are combined to form a complex sulfate system. During the hydration process, ettringite microcrystals are continuously generated, producing a moderate micro-expansion effect, which counteracts the drying shrinkage of calcium oxide during hydration and avoids cracking and strength reduction of the solidified body.
5. The multi-solid waste synergistic solidification agent adapted to high-sulfur heavy metal composite pollution according to claim 1, characterized in that: The fly ash, aluminosilicate, and aluminum silicate are used as raw materials for activated silica-alumina solid waste. Under the alkaline activation of calcium oxide, they polymerize to form a three-dimensional gel network, simultaneously realizing the disposal of industrial solid waste and the reinforcement of high-alumina soil structure.
6. The multi-solid waste synergistic composite solidification agent adapted to high-sulfur heavy metal composite pollution according to claim 1, characterized in that: The sodium polyacrylate is a dry powder dispersing and water-retaining agent used to break up the agglomeration structure of ultrafine powders and nanoparticles, uniformly release gelling and polymerization activities, and moderately regulate the hydration reaction rate to extend the workable window period for construction.
7. The multi-solid waste synergistic solidification agent adapted to high-sulfur heavy metal composite pollution according to claim 1, characterized in that: The sodium diethyldithiocarbamate forms stable, insoluble chelate precipitates with heavy metal ions such as Pb, Cd, Zn, Cu, and Hg. These precipitates are then physically encapsulated and blocked by a silica-alumina gel framework, forming a dual heavy metal stabilization mechanism that combines chemical chelation fixation with physical framework closure.
8. The multi-solid waste synergistic solidification agent adapted to high-sulfur heavy metal composite pollution according to claim 1, characterized in that: By adopting a weak reduction stabilization system to replace the strong oxidation solidification system, it is suitable for industrial complex pollution conditions with high sulfur and heavy metal superposition, effectively avoiding the technical defects of sulfur component oxidation decomposition, heavy metal chelation structure failure, and secondary leaching of pollutants.
9. The application of the multi-solid waste synergistic solidification agent adapted to high-sulfur heavy metal composite pollution as described in any one of claims 1 to 8, characterized in that: It is used for in-situ remediation of coking sites with high sulfur and heavy metal contamination, stabilization and disposal of desulfurized calcium sulfite solid waste, and simultaneous treatment of high aluminosilicate contaminated soil structure improvement and heavy metal pollution.
10. The application of the multi-solid waste synergistic composite solidification agent adapted to high-sulfur heavy metal composite pollution according to claim 9, characterized in that, Different dosages are matched for different pollution conditions: for sites with severe high sulfur and heavy metal coking pollution, the dosage of solidifying agent is 8% of the dry mass of the contaminated soil; for sites with desulfurization solid waste and high sulfur and heavy metal composite pollution, the dosage of solidifying agent is 6% of the dry mass of the contaminated matrix; for sites with moderate to light high sulfur and heavy metal composite pollution, the dosage of solidifying agent is 5% of the dry mass of the contaminated matrix.
Citation Information
Patent Citations
Heavy metal curing agent for treating arsenic-containing fly ash and application thereof
CN119113470A